Navigating Government Websites: Optimizing Information Architecture on the US Department of Labor Site - (:unkn) unknown (Springer Nature Switzerland, 2024)
Government websites serve as sources of information and services related to public affairs, playing an essential role in connecting citizens with government institutions. The responsibility of government websites extends beyond just providing information...
Keywords: Arquitectura de información; Sitios web gubernamentales